PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS SLOGAN DAN POSTER SISWA KELAS VIII SMP NEGERI 30 PADANG - Nurshashikin, Nurshashikin; Gani, Erizal; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The aim of this research is to analyze the effect of implementation PBL learning model toward writing slogan and poster skill eighth grade students of SMP Negeri 30 Padang. This research is quantitative research with quasi experiment method and used the one group pretest-postest design. The research population and sample was the eighth grade students of SMP Negeri 30Padang in the academic year 2017/2018. The samplingtechnique usedispurposive sampling, the obtainable based on the sampling technique are VIII .2 class as sample of this research. The result of this research is there was a significant effect of the implementation of PBL learning model toward writing a report of observation skill eighth grade students of SMP Negeri 30 Padang by freedom degree (n1 + n2)-2 with significants rate 95% and tobservationisbiggerthanttabel thatis9,78>1,70. It means, PBL learning model was effective use in writing slogan and posterskill eighth grade students of SMP Negeri 30 Padang. Observe the benefit and effectiveness of PBL learning model, it proved that PBL learning model can use as reference and developing of inovation toward writing slogan and poster skill.Â Kata kunci: keterampilan menulis, model problem based learning, slogan dan poster